U.S. Dollar Dynamics : How Important Are Policy Divergence and FX Risk Premiums? - Balakrishnan, Ravi (IMF Working Papers; Working Paper ;, 2016)
We investigate the drivers of dynamics of major U.S. FX bilaterals. We first construct a novel measure of FX risk premiums using Consensus exchange rate forecasts. We then use VAR analysis to show that (i) risk premium shocks play a key role in driving dynamics of the major U.S. FX bilaterals; (ii) longer-term interest differentials also matter, especially for the Canadian USD and the Euro; (iii) oil price shocks play a particularly important role for the Canadian USD (an oil exporter); and (iv) risk appetite shocks (e.g., VIX shocks) generally lead to U.S. dollar appreciation. The importance of risk premium and longer-term interest differential shocks fit well with a simple theoretical model and are supported by recent event studies.